PENGARUH KEADILAN PROSEDURAL DAN DISTRIBUTIF TERHADAP KINERJA PEGAWAI DIMEDIASI EMPLOYEE ENGAGEMENT PADA KANTOR PELAYANAN PAJAK PRATAMA SALATIGA - Putra, Hereg Suswanto; Indarto, Indarto; Budiati, Yuli; Savitri, Fania Mutiara (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2023)
Employees who work in the tax service office are required to perform well for the benefit of the institution espescially to increase state revenue. This study purpose to analyze the relationship between procedural and distributive justice on the employee’s performance of Salatiga Pratama Tax Service Office (KPP) with Employee engagement as a mediating variable. This study used a quantitative method using a questionnaire to collect the data. The sample in this study is 105 obtained through the census method. The analysis used to process the data is regression analysis with SPSS 25. The results of this study indicate that procedural justice, distributive justice and Employee engagement affect employee performance. Procedural justice and distributive justice also influence Employee engagement. Furthermore, Employee engagement is able to mediate the relationship between procedural justice and distributive justice on employee performance.